2020
DOI: 10.1097/wnp.0000000000000813
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Electroencephalography After Pediatric Anterior Circulation Stroke

Abstract: Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…We have previously identified that alpha and beta power are reduced in regions of anterior circulation in children with AIS not specifically undergoing ECMO support [ 36 ]. We did not observe asymmetry of alpha or beta power to be associated with AIS in this study.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously identified that alpha and beta power are reduced in regions of anterior circulation in children with AIS not specifically undergoing ECMO support [ 36 ]. We did not observe asymmetry of alpha or beta power to be associated with AIS in this study.…”
Section: Discussionmentioning
confidence: 99%
“…New EEG abnormalities, such as focal slowing or new interictal or ictal activity, can be the first indicator of injury in critically ill children who may otherwise have a limited neurologic examination. The roles of both cEEG and qEEG specifically for detection of ischemia and hemorrhage are reviewed elsewhere in this issue in the article titled “Neuromonitoring in Children With Neurovascular Disorders.” A single-center study of children with acute unilateral anterior circulation ischemic stroke ( n = 5) and hemorrhagic stroke ( n = 6) compared qEEG features between the injured and uninjured hemispheres [ 182 ]. Patients with ischemic stroke demonstrated decreased alpha and beta power and lower spectral edge frequency in the injured hemisphere, whereas patients with hemorrhage consistently had a negative correlation between total power and mean arterial blood pressure.…”
Section: Quantitative Eegmentioning
confidence: 99%
“…DAR), α and δ power ratio (alpha-delta power ratio, ADR), δ+ θ and α+β power ratio [(delta+ theta)/(alpha+ beta), DTABR], as well as relative α wave power (relative alpha power, RAP), relative δ wave power (relative delta power, RDP), and brain symmetry index (brain symmetry index, BSI). Studies have found [21] that δ wave index, slow wave index, θ wave index, BSI, ADR, and DTABR, the six main indicators, are correlated with NIHSS scores. Therefore, this article collects these 6 QEEG features of patients as indicators to determine ischemic stroke, as shown in Table 2.…”
Section: D-d D-dimermentioning
confidence: 99%